Cancerous pH‐responsive polycarboxybetaine‐coated lipid nanoparticle for smart delivery of siRNA against subcutaneous tumor model in mice. Issue 12 (3rd October 2022) - Sung, Yi‐Jung; Guo, Haochen; Ghasemizadeh, Aria; Shen, Xin; Chintrakulchai, Wanphiwat; Kobayashi, Motoaki; Toyoda, Masahiro; Ogi, Koichi; Michinishi, Junya; Ohtake, Tomoyuki; Matsui, Makoto; Honda, Yuto; et al.
Abstract: Lipid nanoparticles (LNPs) have been commonly used as a vehicle for nucleic acids, such as small interfering RNA (siRNA); the surface modification of LNPs is one of the determinants of their delivery efficiency especially in systemic administration. However, the applications of siRNA‐encapsulated LNPs are limited due to a lack effective systems to deliver to solid tumors. Here, we report a smart surface modification using a charge‐switchable ethylenediamine‐based polycarboxybetaine for enhancing tumor accumulation via interaction with anionic tumorous tissue constituents due to selective switching to cationic charge in response to cancerous acidic pH. Our polycarboxybetaine‐modified LNP could enhance cellular uptake in cancerous pH, resulting in facilitated endosomal escape and gene knockdown efficiency. After systemic administration, the polycarboxybetaine‐modified LNP accomplished high tumor accumulation in SKOV3‐luc and CT 26 subcutaneous tumor models. The siPLK‐1‐encapsulated LNP thereby accomplished significant tumor growth inhibition. This study demonstrates a promising potential of the pH‐responsive polycarboxybetaine as a material for modifying the surface of LNPs for efficient nucleic acid delivery. Abstract : Schematic illustration of DSPE‐PGlu(DET‐Car)30 and siRNA‐encapsulated PGlu(DET‐Car)30 LNPs